2019
DOI: 10.1007/s12020-019-01910-3
|View full text |Cite
|
Sign up to set email alerts
|

miR-650 promotes motility of anaplastic thyroid cancer cells by targeting PPP2CA

Abstract: Purpose Aberrant expression of miRNAs is crucial in several tissues tumorigenesis including thyroid. Recent studies demonstrated that miR-650 plays different role depending on the cancer type. Herein, we investigated the role of miR-650 in thyroid carcinoma. Methods The expression of miR-650 was analyzed in human thyroid tissues by q-RT-PCR. Anaplastic (8505C, CAL62, SW1736) and papillary (TPC-1) thyroid cancer cell lines were used to dissect the role of miR-650 on malignant hallmarks of transformation. Label-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 50 publications
(55 reference statements)
0
22
0
Order By: Relevance
“…Wound healing and Transwell assays were performed to evaluate the effect of miR-622 on cell migration ability as previously described. 27 …”
Section: Methodsmentioning
confidence: 99%
“…Wound healing and Transwell assays were performed to evaluate the effect of miR-622 on cell migration ability as previously described. 27 …”
Section: Methodsmentioning
confidence: 99%
“…During the past few decades, the expression profiles of miRNAs in different subtypes of thyroid cancer have been analyzed ( 32 ). A large number of mammalian miRNAs are upregulated in thyroid tumors, such as miR-650 ( 33 ), miR-340-5p ( 34 ), miR-424-5p ( 35 ) and miR-155 ( 36 ); while a number of miRNAs have been reported to be downregulated, such as miR-26a ( 37 ), miR-215 ( 38 ), miR-34a ( 39 ) and miR-206 ( 40 ). In addition, a previous study indicated that the expression levels of numerous miRNAs exhibit significant differences in MTC ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various functional roles of miR-650 are regarded in different tumors, which are dependent on the target genes in a particular histological type ( 28). An elevated miR-650 expression is observed in hepatocellular cancer, lung adenocarcinoma, and prostate cancer, which correlates with tumor metastasis and poor prognosis (29)(30)(31)(32). Nevertheless, the overexpression of miR-650 also indicates favorable survival estimation in chronic lymphocytic leukemia and colorectal cancer (33,34).…”
Section: Discussionmentioning
confidence: 99%